PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT SRIWIJAYA SUMATRA SELATAN - Muhammad Iqbal (Universitas 45 Surabaya, 2022)
This study aims to determine; (1) the working environment conditions at PT Sriwijaya Sumatera Selatan; (2) employee performance at PT Sriwijaya Sumatera Selatan; and (3) is there a significant effect between the work environment on the performance of employees at PT Sriwijaya Sumatera Selatan. This research is quantitative research using regression analysis. The population in this study were all employees of PT Sriwijaya Sumatera Selatan, totalling 10 employees. Sampling with totalling sampling technique. The instrument used is a questionnaire with a Likert scale which has 5 alternative answers. The instrument validity test uses item analysis and is calculated using the product moment formula, while the reliability test uses Cronbach's Alpha formula. Prerequisites for analysis include a normality test and a linearity test. Next, test the hypothesis using simple regression. The results showed that there was a positive and significant influence between the work environment and employee performance at PT Sriwijaya Sumatera Selatan with a correlation coefficient (R) of 0.643 and a coefficient of determination of 0.413. This means that 41.3% of employee performance at PT Sriwijaya Sumatera Selatan is influenced by the work environment, while the other 58.7% is determined by other variables not explained in the study.